Tracing Fasting Glucose Fluxes with Unstressed Catheter Approach in Streptozotocin Induced Diabetic Rats - Shichun Du; Hui Wu; Xiao Xu; Ying Meng; Fangzhen Xia; Hualing Zhai; Yingli Lu (Journal of Diabetes Research)
Objective. Blood glucose concentrations of type 1 diabetic rats are vulnerable, especially to stress and trauma. The present study aimed to investigate the fasting endogenous glucose production and skeletal muscle glucose uptake of Streptozotocin induced type 1 diabetic rats using an unstressed vein and artery implantation of catheters at the tails of the rats as a platform. Research Design and Methods. Streptozotocin (65 mg·kg−1) was administered to induce type 1 diabetic state. The unstressed approach of catheters of vein and artery at the tails of the rats was established before the isotope tracer injection. Dynamic measurement of fasting endogenous glucose production was assessed by continuously infusing stable isotope [6, 6-2H2] glucose, while skeletal muscle glucose uptake by bolus injecting radioactively labeled [1-14C]-2-deoxy-glucose. Results. Streptozotocin induced type 1 diabetic rats displayed polydipsia, polyphagia, and polyuria along with overt hyperglycemia and hypoinsulinemia. They also had enhanced fasting endogenous glucose production and reduced glucose uptake in skeletal muscle compared to nondiabetic rats. Conclusions. The dual catheters implantation at the tails of the rats together with isotope tracers injection is a save time, unstressed, and feasible approach to explore the glucose metabolism in animal models in vivo.